Presentation and Treatments for Mucopolysaccharidosis Type II (MPS II; Hunter Syndrome) - Stapleton, Molly (Expert Opin Orphan Drugs, 2017)
INTRODUCTION: Mucopolysaccharidosis Type II (MPS II; Hunter syndrome) is an X- linked lysosomal storage disorder caused by a deficiency of iduronate-2-sulfatase (IDS). IDS deficiency leads to primary accumulation of dermatan sulfate (DS) and heparan sulfate (HS). MPS II is both multi-systemic and progressive. Phenotypes are classified as either attenuated or severe (based on absence or presence of central nervous system impairment, respectively). AREAS COVERED: Current treatments available are intravenous enzyme replacement therapy (ERT), hematopoietic stem cell transplantation (HSCT), anti-inflammatory treatment, and palliative care with symptomatic surgeries. Clinical trials are being conducted for intrathecal ERT and gene therapy is under pre-clinical investigation. Treatment approaches differ based on age, clinical severity, prognosis, availability and feasibility of therapy, and health insurance. This review provides a historical account of MPS II treatment as well as treatment development with insights into benefits and/or limitations of each specific treatment. EXPERT OPINION: Conventional ERT and HSCT coupled with surgical intervention and palliative therapy are currently the treatment options available to MPS II patients. Intrathecal ERT and gene therapy are currently under investigation as future therapies. These investigative treatments are critical to address the limitations in treatment of the central nervous system (CNS).